Special issue introduction: Actions for the missing: scientific and vernacular forms of war dead accounting - Tâm T. T. Ngô; Sarah Wagner (Human Remains and Violence)
This special issue examines Asian experiences of war and mass death in the previous century, with case studies from China, Japan, Korea and Vietnam (North and South, among its diaspora and across multiple generations). In this introduction we highlight several of the wider analytical interventions offered by the articles: (1) the spatiopolitical dynamics of war dead accounting in which forms of vernacular forensic expertise interact with and inform internationally honed, empirically grounded practices of exhumation and identification; (2) the complex hierarchy of authority over remains that structures programmes of war dead accounting; (3) the variegated (as opposed to monolithic) nature of war dead themselves; and (4) the material ecosystems of remains, graves, cemeteries and the non-human forces of decay acting upon them. Finally, the introduction highlights the issue’s comparative potential: that is, what these different cultural, religious and ideological modes of meaning-making reveal about why and how human remains matter in the aftermath of war – and not just according to Western notions of national memory politics in which the soldier stands in for the state and collective mourning animates the national imaginary.